2019
DOI: 10.15666/aeer/1701_10391048
|View full text |Cite
|
Sign up to set email alerts
|

Norfloxacin Resistant Bacterial Compositions in Sediments of Chinese Subtropical Fish Ponds

Abstract: Antibiotic resistant bacteria are widely spread in environments. However, the compositions of bacteria with antibiotic resistance in subtropical fish pond sediment are still unclear. In present study, to analyze the compositions of norfloxacin resistant bacteria in subtropical fish pond sediments, we selectively cultured the sediment bacteria collected from six subtropical fish ponds located in southern China using the basic medium with 50 µg/ml of norfloxacin, and analyzed their compositions using MiSeq high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The LEfSe method is widely used for the comparative analysis of microbiota compositions in various habitats and for the screening of significantly different microorganisms (Xiang et al, 2018;Li et al, 2019b;Li et al, 2019c;Mao et al, 2019;Liu et al, 2022). However, our results showed that this method could not simultaneously compare the differences between two or more treatment groups and the control.…”
Section: Discussionmentioning
confidence: 66%
“…The LEfSe method is widely used for the comparative analysis of microbiota compositions in various habitats and for the screening of significantly different microorganisms (Xiang et al, 2018;Li et al, 2019b;Li et al, 2019c;Mao et al, 2019;Liu et al, 2022). However, our results showed that this method could not simultaneously compare the differences between two or more treatment groups and the control.…”
Section: Discussionmentioning
confidence: 66%
“…7−10 Norfloxacin (NOR) resistance commonly exists in Gram-negative bacteria in the fish pond sediments located in southern China. 11 Therefore, it is crucial to understand the mechanisms of quinolones in aquaculture pathogens.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The misuse of the antibiotics or dosage to treat common aquatic diseases leads to sublethal antibiotic concentrations and causes the development of mutant multidrug resistance strains. , For example, the antibiotic resistance of quinolones has increased following widespread use and appeared in many fish pathogens. Norfloxacin (NOR) resistance commonly exists in Gram-negative bacteria in the fish pond sediments located in southern China . Therefore, it is crucial to understand the mechanisms of quinolones in aquaculture pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent the disease of cultured fish, antibiotics are widely used in pond high-density and intensive culture, which leads to a large number of antibiotics remain in the pond water and sediment (Mao et al 2019). For instance, Wang et al (2011) reported that fish only absorb about 1/5 of antibiotics in feed, and most of the antibiotics enter the water and sediment.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive use of antibiotics has caused a serious threat of antibiotic resistance (Laxminarayan et al 2013). Although the usage of antibiotics in agricultural production is strictly restricted presently, residues of antibiotics in environment and illegal use of antibiotics still cause prevalence of antibiotic resistance, especially in lakes and fish ponds (Hao et al 2017, Liu and Lu 2018, Mao et al 2019, Lemańska et al, 2021. Liu and Lu (2018) reported that Baiyangdian Lake, Taihu Lake, Chaohu Lake, Wulungu Lake, Besiteng Lake, Daliao River were polluted by a variety of antibiotics.…”
Section: Introductionmentioning
confidence: 99%